A política de desenvolvimento dos territórios rurais: uma leitura preliminar no agreste de Alagoas. - Santos, Leide Maria Reis dos (2009)
This research has as a goal to analyze the effectiveness of the territorial policy directed to the familiar agriculture, having as an analytical reference the delimitation of rural territories observed empirically in the Alagoano Agrestic. The Rural Territories were implemented in 2003 under the charge of the Development Territorial Agrarian Ministry which has as a central aim the social insertion of those who live in the poverty line through the institutionality, representation and innovation. In this sense, this report shows the changes made in the Alagoano Agrestic area through the rural developmental sustainability, highlighting the problems which make impossible the execution of these actions. For the conclusion of this work some data were used, likewise the bibliographical review and some field research work, also done through interviews with some social representatives from entities which make part of this territory. It was observed that despite the consolidation of the commission through the Territorial Development, the problems happened as disputes with the social agents for the income aimed mainly to defined chains (cassava and milk).The fragility of some counties which made part of the commission, the lack of organization, participation and commitment of some counties in not paying their taxes, impeded the approval of the projects and problems related to infrastructure increased , making it difficult to the distribution of the production. Nowadays this territory is included in the citizenship territories program (2008) which consists in an integrated action among many administration departments, making possible not only the enlargement of the resources but also the social participation. It is conclusive that although the section focus (agriculture), the policy of the Rural Territories represented a relative breakthrough for intersecting State and the civil society. The changes happened through projects created collectively, resulting from the restructure of some flour processing units which contributed to a better productivity and quality of the product, as well as to the ongoing construction of a processing milk unit and the implementation of a flour processing and classifying unit in Arapiraca county that along with Palmeira dos Índios play an important influence in that territory.